2013
DOI: 10.1016/j.scr.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

miR-210 suppresses BNIP3 to protect against the apoptosis of neural progenitor cells

Abstract: MiR-210 is a hypoxia-inducible factor (HIF)-1 target gene and is the most consistently and predominantly upregulated miRNA in response to hypoxia in various cancer cell lines. Our recent study shows that hypoxia increased miR-210 expression in neural progenitor cells (NPCs) in a time-dependent manner. However, the role of miR-210 in NPCs remains unknown. Following the identification of the miR-210 putative target genes, we demonstrated that the Bcl-2 adenovirus E1B 19kDa-interacting protein 3 (BNIP3), which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 31 publications
4
50
0
3
Order By: Relevance
“…Based on previous studies showing that excessive accumulation of ROS has been shown to damage stem cells through JNK-and caspase-mediated mechanisms [23], it could be suggested that over-expression of miR-210 in MSCs decreased intracellular oxidative reactions through the activation of the c-Met pathway, thus leading to an obvious improvement of cell viability under oxidative stress. In stem cells, miR-210 might play a critical function that links apoptosis signals to the oxidative stress microenvironment, which is the vital finding in our study and was consistently shown by previous reports [24,25]. Favaro et al [21] showed that ROS accumulation could be alleviated with antimiR-210 treatment in cancer cell lines.…”
Section: Discussionsupporting
confidence: 88%
“…Based on previous studies showing that excessive accumulation of ROS has been shown to damage stem cells through JNK-and caspase-mediated mechanisms [23], it could be suggested that over-expression of miR-210 in MSCs decreased intracellular oxidative reactions through the activation of the c-Met pathway, thus leading to an obvious improvement of cell viability under oxidative stress. In stem cells, miR-210 might play a critical function that links apoptosis signals to the oxidative stress microenvironment, which is the vital finding in our study and was consistently shown by previous reports [24,25]. Favaro et al [21] showed that ROS accumulation could be alleviated with antimiR-210 treatment in cancer cell lines.…”
Section: Discussionsupporting
confidence: 88%
“…The authors concluded that miR-210 is a novel predictive serum biomarker for preeclampsia. Wang et al [18] reported expression of miR-210 in neural progenitor cells, whereby they identified Bcl-2 adenovirus E1B 19 kDa-interacting protein 3 (BNIP3), which is regulated by HIF-1α and promotes cell death, as a direct functional target of miR-210. MiR-210 directly suppressed BNIP3 expression, which subsequently reduced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ischemia preconditioning enhances bone marrow-derived mesenchymal stem cells (MSCs) survival via induced expression of miR-210, whereas miR-210 knockdown increases caspase-8-associated protein-2 (CASP8AP2) levels, a regulator in Fas-mediated apoptosis, resulting in enhanced cell apoptosis after ischemia [87]. Consistent with this finding, a recent study reported that upregulation of miR-210 during hypoxia decreased in NPC apoptosis as a result of inhibition of Bcl-2 adenovirus E1B 19kDa-interacting protein 3 (BNIP3) [88]. However, in contrast to the findings that miR-210 promotes cell survival, Chio and colleagues reported that miR- 210 directly targeted the 3' untranslated region (UTR) of the antiapoptotic gene Bcl-2, thereby enhancing the hypoxia-induced apoptosis of neuroblastoma cells treated with oxygen/glucose deprivation [89].…”
Section: Epigenetic Mechanisms and The Machineriesmentioning
confidence: 84%